Creatine - new hope in cancer treatment - Wojciech Mądry; Aleksandra Mazurkiewicz; Justyna Marcicka; Magdalena Kołodziej; Joanna Męczyńska; Nazarii Saiuk; Michał Andrzej Kozicz; Tomasz Seredyński; Adriana Wojciechowska; Weronika Salasa (Kazimierz Wielki University, 2024)
Introduction Creatine, a supplement popular especially among athletes, is gaining increasive attention from scientists worldwide due to its potential health benefits, among other things, in the context of its anti-cancer application. Materials and methods The following review of studies is based on scientific articles from recent years available in the PubMed and Google Scholar databases. Key search terms included: "creatine", "creatine supplementation", "creatine in sports", "supplementation in sports", "creatine in cancer". Results The literature review unequivocally demonstrates the beneficial impact of creatine supplementation on numerous health and athletic aspects. Creatine has been observed to have a positive effect on selected aspects of cancer treatment, such as reducing tumor mass, complementing the action of commonly used anticancer drugs, and slowing down the wasting associated with cancer diseases. Conclusion The promising results of the cited studies indicate that further research into creatine supplementation and its mechanisms of action is necessary. There is a need for further research on the positive impact of creatine supplementation in the treatment of cancer diseases. The significant potential of creatine supplementation may enable its inclusion in clinical practice in the future and the development of an effective therapeutic strategy based on it in the treatment of cancer diseases.